PENYELESAIAN TERHADAP DEBITUR WANPRESTASI DALAM PERJANJIAN GADAI - Asuan, Asuan (Solusi, 2020)
The problem of this research is how the default in the pawn agreement and settlement of the debtor default in the pawn agreement according to the Civil Code. One type of guarantee for movable objects is a pawn given to guarantee a bill or credit that is regulated in article 1150 of the Civil Code (Civil Code). Default is not fulfilling something that is required as specified in the agreement. Debtor defaults in a pawn agreement according to Article 1234 of the Civil Code, that one of the defaults is caused by not doing what he is promised to do. Article 1238 of the Civil Code states that the debtor is considered negligent with the passing of the time limit specified as stated in the Credit Proof (SBK) approved by the debtor and creditor, in a pawn agreement there is a need for a warning or reprimand / summons. Settlement of default debtors in the pawn agreement according to the Civil Code is contained in article 1156 paragraph 1 and 2, namely through auctions of pawning goods generally called direct execution (parate execution) and submit a claim through the local District Court in accordance with where the debtor entered into a pawn agreement.